2014
DOI: 10.3109/09637486.2014.886184
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of anthocyanins-rich extract from bilberry (Vaccinium myrtillusL.) on croton oil-induced ear edema andPropionibacterium acnesplus LPS-induced liver damage in mice

Abstract: Bilberry (Vaccinium myrtillus L.) has been known to play a protective role in human health due to its high anthocyanin content. This study investigated the anti-inflammatory effects of bilberry extract (BE, containing 42.04% anthocyanin) on Propionibacterium acnes (P. acnes) plus lipopolysaccharide (LPS) induced liver injury and croton oil-induced ear edema in mice. Results showed that BE could effectively inhibit croton oil-induced ear edema and liver inflammation provoked by P. acnes plus LPS, as reflected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 40 publications
2
30
0
1
Order By: Relevance
“…However, it should be kept in mind that the treatment with ANT reduced the NOx levels in the EB groups (Fig. 2C), and this appears to agree with the studies that showed berry ANT suppressed the expression iNOS, TNF-α, IL6 and IL-1β in the liver [111,112] and the secretion of proinflammatory mediators by the macrophage inhibition of NF-kappaB [113].…”
Section: Discussionsupporting
confidence: 87%
“…However, it should be kept in mind that the treatment with ANT reduced the NOx levels in the EB groups (Fig. 2C), and this appears to agree with the studies that showed berry ANT suppressed the expression iNOS, TNF-α, IL6 and IL-1β in the liver [111,112] and the secretion of proinflammatory mediators by the macrophage inhibition of NF-kappaB [113].…”
Section: Discussionsupporting
confidence: 87%
“…These compounds play a 32 role in attracting animals in pollination and seed dispersal; they 33 may also enhance plant resistance to insect attack, act as 34 endogenous plant antioxidants and photoprotectors (Strack and 35 Wray, 1993;Delgado-Vargas et al, 2000). Evidence also suggests 36 that this group of phytochemicals, besides being nontoxic and 37 non-mutagenic, could exhibit multiple biological effects, such as 38 antioxidant activity, anti-inflammatory action, inhibition of blood 39 platelet aggregation, and antimicrobial activity, and could be used 40 in the treatment of diabetic retinopathy and prevention of 41 cholesterol-induced atherosclerosis (Luo et al, 2014;Pascual-42 Teresa et al, 2013;Zheng and Wang, 2003). 43 Sweet potato is the root of Ipomoea batatas (L.) Lam.…”
Section: Q2mentioning
confidence: 96%
“…Anthocyanin in bilberry extract is a highly soluble antioxidant with a flavylium ion structure [21]. It is found in the ocular tissues [22] and suppresses various inflammatory factors in the body [23]. Because it is possible that anthocyanins migrate and are distributed from the blood to the ciliary muscle, they can suppress and relieve the tension in the ciliary muscle, thereby potentially reducing ocular fatigue.…”
Section: Discussionmentioning
confidence: 99%